2005
DOI: 10.1074/jbc.m500687200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adsorption to Aluminum Salt Adjuvants on the Structure and Stability of Model Protein Antigens

Abstract: The effect of adsorption onto aluminum salt adjuvants on the structure and stability of three model protein antigens was studied using fluorescence and Fourier transform infrared spectroscopies, as well as isothermal titration and differential scanning calorimetric techniques. Lysozyme was preferentially adsorbed to aluminum phosphate (Adju-Phos®), whereas ovalbumin and bovine serum albumin were better adsorbed to aluminum hydroxide (Alhydrogel®). A linearized Langmuir adsorption isotherm was used to obtain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
172
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(183 citation statements)
references
References 21 publications
10
172
1
Order By: Relevance
“…7). It has been reported that interactions of protein antigens with the highly charged aluminum salts may destabilize their structures (81). Consistent with this finding, MPERp in contact with alum underwent significant aggregation, as denoted by the IR absorption at 1620 cm Ϫ1 (Fig.…”
Section: Figure 8 Recovered Responses After Vaccination With the Popsupporting
confidence: 76%
“…7). It has been reported that interactions of protein antigens with the highly charged aluminum salts may destabilize their structures (81). Consistent with this finding, MPERp in contact with alum underwent significant aggregation, as denoted by the IR absorption at 1620 cm Ϫ1 (Fig.…”
Section: Figure 8 Recovered Responses After Vaccination With the Popsupporting
confidence: 76%
“…This probably reflects the particular robust structure of these VLPs, as adsorption to aluminum can result in more drastic changes in thermal stability with other antigens. 28 Nevertheless, a minor contribution could be detected and was attributed to a pre-transition at slightly lower temperature, requiring less energy, while the main transition Tm remained unaffected. Such remarkable conformational robustness can account, at least in part, for the excellent long-term stability of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, conformational changes may also occur when a vaccine is adsorbed to the adjuvant that affect its antigenicity. Jones et al [16] found significant changes in the shape of ATR-FTIR spectra for bovine serum albumin, lysozyme and ovalbumin upon adsorption to aluminum adjuvants. Those authors concluded that a disruption of antigen conformation caused by adsorption destabilized the proteins' structures, and proposed that this phenomenon may itself contribute to the adjuvant effect.…”
Section: Discussionmentioning
confidence: 99%
“…To yield adequate signal, the method we employed required higher protein concentrations than were present in the formulation for vaccination (0.7-0.9 mg/mL versus 0.2 mg/mL), but much less than is typically used in transmission FTIR (>10 mg/mL), or HATR on protein/adjuvant mixtures without deuteration (≥2 mg/mL) [16]. We used protein concentrations as low as possible in order to prevent the appearance of artifacts due to self-association at high concentration.…”
Section: Conformation Of Vaccine Adsorbed To Adjuvantmentioning
confidence: 99%